The effect of nano-TiO2 and SiO2 on bonding strength and structural properties of poly (vinyl acetate) composites - Bardak, Timuçin; Tankut, Ali Naci; Tankut, Nurgül; Sözen, Eser; Aydemir, Deniz; Bardak, Timuçin; Sözen, Eser; Aydemir, Deniz (Elsevier, 2016)
Polyvinyl acetate (PVAc) is a thermoplastic polymer widely used in the furniture industry. It has many advantages such as easy processing, cheap, biodegradable; but, resistance to water and hot medium is not enough to the application area. In this study, the effect of nano-TiO2 and nano-SiO2 on bonding performance and structural properties of PVAc were investigated. Bonding strength with block shear test and structural properties with thermogravimetric analysis-TGA, X-ray diffraction-XRD, and transmission electron microscopy-TEM of PVAc were determined. The obtained results showed that bonding strength with cooperating both TiO2 and SiO2 for 1% and 2% were improved. XRD and TEM results proved to be the homogenously interactions for 1% and 2% between nano fillers and matrix. TGA results showed that thermal stability of PVAc blends was largely improv
Keywords: Poly (vinyl acetate); Nanomaterials; Thermal gravimetric analysis; Biodegradable polymer; Bonding performance